Inventory management strategies that reduce the age of red blood cell components at the time of transfusion. Issue 7 (17th May 2016) - Poisson, Jessica L.; Tuma, Christopher W.; Shulman, Ira A.
Abstract : BACKGROUND: There has been interest concerning patient outcomes when older red blood cell (RBC) components are utilized. Inventory management is key to maintaining a stock of fresher RBCs for general transfusion needs. We have altered our practice for RBC management to reduce RBC age at the time of transfusion. STUDY DESIGN AND METHODS: Retrospective review of RBC age at time of transfusion at a tertiary care hospital with active trauma service was performed. The baseline nonirradiated RBC inventory was decreased from 12 to 15 days of stock to 7 to 10 days of stock, with request made to the blood supplier for fresher RBCs, specified at 75% of RBCs less than 14 days old. The age of RBCs at time of receipt and at time of transfusion was tracked on a monthly basis for the next 12 months. RESULTS: The mean age of RBCs at transfusion was decreased by 9 days on average for the year. Significant decreases in the mean age of RBCs at transfusion were seen in the second half of the year, with 4 of 6 months seeing a mean age of less than 20 days. There were no documented incidences of hospital blood shortages after the reduction in inventory; no surgery was canceled or delayed because of inventory. CONCLUSION: Inventory age depends on active management, combined with vendor cooperation to receive fresher components. Reducing the age of RBC components transfused is possible without experiencing blood component shortages. Longer periods of observation may allow for further adjustment of stocking levels on a seasonal basis.